Identification and Virulence of Cordyceps javanica Strain wf GA17 Isolated From a Natural Fungal Population in Sweetpotato Whiteflies (Hemiptera: Aleyrodidae). Issue 5 (25th June 2021) - Wu, Shaohui; Toews, Michael D; Castrillo, Louela A; Barman, Apurba K; Cottrell, Ted E; Shapiro-Ilan, David I
Abstract: A new strain of the entomopathogenic fungus, identified as Cordyceps javanica (Frieder. & Bally) Kepler, B. Shrestha & Spatafora (Hypocreales: Cordycipitaceae) wf GA17, was found naturally infecting the sweetpotato whitefly, Bemisia tabaci (Gennadius) MEAM1 in southern Georgia, US, in September 2017. The fungus was tested for pathogenicity and virulence in comparison with commercially available entomopathogenic fungal strains against several insect species in the laboratory. In specific, it was compared with Cordyceps fumosorosea (Wize) Kepler, B. Shrestha & Spatafora (Hypocreales: Cordycipitaceae) Apopka 97, Beauveria bassiana (Bals.-Criv.) Vuill. (Hypocreales: Cordycipitaceae) strain GHA, and Metarhizium brunneum Petch (Hypocreales: Clavicipitaceae) strain F52 for virulence against B. tabaci (4 th instars) and cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae) (4 th instars with or without wingbuds), on leaf-discs, and against last instars of pecan weevil Curculio caryae (Horn) (Coleoptera: Curculionidae) and citrus root weevil Diaprepes abbreviatus (L.) (Coleoptera: Curculionidae) in soil cups. Against B. tabaci, C. javanica exhibited higher mortality and mycosis development at 5 d post inoculation than other fungi. In assays against A. gossypii with and without wingbuds, C. javanica and C. fumosorosea had the highest mortality and mycosis levels and B. bassiana had the lowest; nymphs with wingbuds were more susceptible to some fungal infection than those without. Against C. caryae, B. bassiana was more effective than other fungi. For D. abbreviatus, B. bassiana also caused the highest mortality while M. brunneum had the lowest, with Cordyceps spp. being intermediate. Overall, the findings suggest high potential of the new strain, C. javanica wf GA17, for managing whiteflies and aphids, while it was not as effective as B. bassiana against the curculionids.